TI_GERICHTE 52.2022.410 vom 9. November 2022 , Licenza edilizia a posteriori per la modifica della sistemazione esterna - TI Tribunale d'appello (2022)
Licenza edilizia a posteriori per la modifica della sistemazione esterna